Toward to “Green Deal” Legal and Natural Aspects of the Development of Small Hydropower Plants - The Example of Poland - Marszelewski, Michal; Piasecki, Adam (International Journal of Energy Economics and Policy, 2022)
The article contains a legal-environmental analysis covering the development and operational aspects of small hydropower plants (SHPs) in Poland. From legal perspective, the paper presents conditions that have to be met during the investment process. It was shown that such a process is highly formalized. The need to protect the water and the environment results in necessity to obtain various administration decisions like water permits or decision on environmental conditions. Second discussed law-related field is the support system. In Poland there are three categories of SHPs support system: green certificates, auction system and feed-in tariff (FIT) or feed-in premium (FIP) system. The last one is the most optimal for SHPs and significantly helps to make them profitable. Moving on to an environmental perspective, Polish topography is relatively unfavorable for SHPs because of water resources and significant part of flat lowlands. Taking into account that SHP may have a visible impact on ecosystems and – in most cases – are localized and managed by private entities, it is crucial to use the SHPs potential in Poland as effective as possible. Conducted analysis also shown the legal regulation should be changed to more friendly for SHPs operators.